2006
DOI: 10.1021/jp057194v
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Landing Isolation of Vanadium−Benzene Sandwich Clusters on a Room-Temperature Substrate Using n-Alkanethiolate Self-Assembled Monolayer Matrixes

Abstract: Gas-phase synthesized vanadium-benzene 1:2 (VBz(2)) sandwich clusters were size-selectively deposited onto bare gold and long-chain n-alkanethiolate [-S-(CH(2))(n-1)-CH(3); n = 16, 18, and 22] self-assembled monolayer (SAM)-coated gold substrates under ultrahigh vacuum (UHV) conditions. Investigation of the resulting deposited clusters was performed by infrared reflection absorption spectroscopy (IRAS) and thermal desorption spectroscopy (TDS). The IR frequencies of the soft-landed VBz(2) clusters show excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
96
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 24 publications
5
96
0
Order By: Relevance
“…[12][13][14] For instance, a recent study by Nakajima and co-workers demonstrated facile matrix isolation of vanadium-benzene sandwich clusters through ion soft landing. [15] In addition, a previous publication from our group describes an investigation of the charge retention and neutralization behavior of organometallic metal-salen complexes soft landed onto 1H,1H,2H,2H-perfluorododecane-1-thiol (FSAM) and 1-dodecanethiol self-assembled monolayer (HSAM) surfaces on gold. [16] More recently, in a collaborative study, we demonstrated that acid-mediated redox chemistry may be observed in thin films of organometallic complexes prepared by ion soft landing.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] For instance, a recent study by Nakajima and co-workers demonstrated facile matrix isolation of vanadium-benzene sandwich clusters through ion soft landing. [15] In addition, a previous publication from our group describes an investigation of the charge retention and neutralization behavior of organometallic metal-salen complexes soft landed onto 1H,1H,2H,2H-perfluorododecane-1-thiol (FSAM) and 1-dodecanethiol self-assembled monolayer (HSAM) surfaces on gold. [16] More recently, in a collaborative study, we demonstrated that acid-mediated redox chemistry may be observed in thin films of organometallic complexes prepared by ion soft landing.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, peptides and proteins are typically ionized by protonation and lose charge by releasing protons to the SAM. In contrast, native cations such as organometallic complexes undergo charge reduction through electron transfer from the underlying metal surface 200,201. In the case of multiply charged cationic gold clusters, we demonstrated that the charge may be controlled by changing the terminal functionality of the monolayer as well as the coverage of ions 152,153.…”
mentioning
confidence: 92%
“…To date, a multitude of techniques have been applied for this purpose including secondary ion mass spectrometry (SIMS) 19,[97][98][99][100] , temperature programmed desorption and reaction 50,52 , laser desorption and ionization 101 , pulsed molecular beam reaction 102 , infrared spectroscopy (FTIR and Raman) 98,103,104 , surface enhanced Raman spectroscopy 103,105 , cavity ringdown spectroscopy 106 , xray photoelectron spectroscopy 35,107 , scanning tunneling microscopy 33,[108][109][110][111] , atomic force microscopy [112][113][114] , and transmission electron microscopy 39 . However, to most accurately characterize surfaces prepared or modified by ion soft landing, it is crucial that the analysis be performed in situ without exposure of the substrate to the environment in the laboratory.…”
Section: Introductionmentioning
confidence: 99%